CAPITAL AND THE MONETARY BUSINESS CYCLE THEORY : ESSAYS ON THE AUSTRIAN THEORY OF CAPITAL, INTEREST, AND BUSINESS CYCLE - Potužák, Pavel; Kadeřábková, Božena; Holman, Robert, 1953-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
This dissertation explores four big topics in the Austrian economic theory. Chapter 1 elucidates the Austrian theory of capital. It introduces basic tools that are further used in the analysis of the business cycle. It also clarifies some misunderstandings in this theory. Chapter 2 investigates the evolution of the interest rate over the business cycle that is predicted by the Austrian theory of economic fluctuations. Chapter 3 examines the pure time preference theory. It shows with the help of a simple neoclassical graphical and mathematical apparatus that there is a fundamental flaw in this theory. It suggests that the notions of want and good must be explicitly separated, and it concludes that the time preference as well as the subjective exchange ratio between present goods and future goods may take on any value. Chapter 4 explores the business cycle dynamics in the economy with permanently rising natural output. Simple monetary policy rule that was designed to eliminate economic fluctuations is discussed in detail.
Vedoucí práce: Božena Kadeřábková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby
Způsob přístupu: Internet
Keywords: hospodářská politika [obor disert. práce]; disertace; dissertations